2021
DOI: 10.3390/ijerph18105138
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Music Therapists’ Practice to the Outset of the COVID-19 Pandemic—Going Virtual: A Scoping Review

Abstract: Background: In the midst of a worldwide COVID-19 pandemic, music therapists previously not involved in telehealth had to develop effective remote forms of music therapy. The objective of this review was to systematically explore how music therapists previously working in-person adapted to the transfer to remote forms of therapy in the context of the coronavirus outbreak. Methods: We searched Scopus, Web of Science Core Collection, CINAHL, Medline, ProQuest Central, PubMed, EMBASE, PsycINFO and PsyARTICLES, gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
3
29
0
4
Order By: Relevance
“…Specifically, during the COVID-19 pandemic, many music therapists showed uncertainty regarding the RAS methods application in telemedicine, linked to the increased risk of falling and the lack of physical support [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, during the COVID-19 pandemic, many music therapists showed uncertainty regarding the RAS methods application in telemedicine, linked to the increased risk of falling and the lack of physical support [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the specificity of this new approach could be challenging, such as Internet connection problems, familiarity of patients and CG with these modern technologies, breaks in the line, strange sounds, asynchronous harmony and rhythm, overlapping speech and call disconnections. MT as a relationship therapy can lack important aspects based on physical contact when transferred to virtual space [ 13 , 14 , 30 ]. For these reasons, many patients may refuse this practice rather than using it with a poor quality level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More scientific evidence about VMT was published after the beginning of the pandemic. We conducted a scoping review and found 10 articles published from the onset of the pandemic to the 25 th October 2020 (Kantorová et al, 2021). Moreover, we described different adaptations to music therapy practice, including adaptations to the goals, methods/techniques, space, musical instruments, technologies, flexibility and logistics, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing these challenges requires the knowledge of specific adaptations (Berman, 2020;Knott & Block, 2020). Although there is only limited scientific evidence for VMT (Kantorová et al, 2021), it is desirable to implement previously mentioned recommendations in therapy practice and ensure the highest possible quality of music therapy carried out in the virtual environment.…”
mentioning
confidence: 99%